Luteolin inhibits GPVI-mediated platelet activation, oxidative stress, and thrombosis - Ye, Yujia; Yang, Lihong; Leng, Min; Wang, Qian; Wu, Jiankui; Wan, Wen; Wang, Huawei; Li, Longjun; Peng, Yunzhu; Chai, Shengjie; Meng, Zhaohui (Frontiers in Pharmacology, 2023)
Luteolin inhibits platelet activation and thrombusosis formation, but the mechanisms are unclear. This study investigated the effects of luteolin on GPVI-mediated platelet activation in vitro and explored the effect of luteolin on thrombosis, coagulation, and platelet production in vivo. Washed human platelets were used for aggregation, membrane protein expression, ATP, Ca2+, and LDH release, platelet adhesion/spreading, and clot retraction experiments. Washed human platelets were used to detect collagen and convulxin-induced ROS production and endogenous antioxidant effects. C57BL/6 male mice were used for ferric chloride-induced mesenteric thrombosis, collagen-epinephrine-induced acute pulmonary embolism, tail bleeding, coagulation function, and luteolin toxicity experiments. The interaction between luteolin and GPVI was analyzed using solid phase binding assay and surface plasmon resonance (SPR). Luteolin inhibited collagen- and convulxin-mediated platelet aggregation, adhesion, and release. Luteolin inhibited collagen- and convulxin-induced platelet ROS production and increased platelet endogenous antioxidant capacity. Luteolin reduced convulxin-induced activation of ITAMs and MAPK signaling molecules. Molecular docking simulation showed that luteolin forms hydrogen bonds with GPVI. The solid phase binding assay showed that luteolin inhibited the interaction between collagen and GPVI. SPR showed that luteolin bonded GPVI. Luteolin inhibited integrin αIIbβ3-mediated platelet activation. Luteolin inhibited mesenteric artery thrombosis and collagen-adrenergic-induced pulmonary thrombosis in mice. Luteolin decreased oxidative stress in vivo. Luteolin did not affect coagulation, hemostasis, or platelet production in mice. In conclusion, luteolin may be an effective and safe antiplatelet agent target for GPVI. A new mechanism (decreased oxidative stress) for the anti-platelet activity of luteolin has been identified.